Embedded Based Quadratic Boost Converter with Sliding Mode Controller for the integration of Solar Photo-Voltaic source with Microgrid - S, Chitra Selvi; Govindaraj, Ramya; Chowdhury, Subrata; Singh, Saumya; Khan, Baseem (Institute of Electrical and Electronics Engineers Inc., 2023)
A microgrid is a free-standing electrical network consisting of several energy sources and loads meant for specific applications or localized areas of operation. Power electronic converters are used in a microgrid for interfacing electrical sources and electrical loads of different power and voltage ratings with the standard bus bars of the microgrid. Microgrids use renewable energy sources like the wind and solar photovoltaic energy source, and the fuel cell-based energy conversion systems. DC to DC converters is inevitable in a microgrid. The Quadratic Boost Converter (QBC) is a high voltage gain DC to DC converter with a single power electronic switch. In this work, the applicability of the Sliding Mode Controller (SMC) for the maximized harvest of energy from a solar photovoltaic system using the QBC is studied. Further, the capability of the QBC, along with an SMC, for the regulation of voltage across the terminals of the load, when the QBC acts as an interface between a load and the bus bar of the microgrid is also investigated. Relevant dynamic equations are derived from fundamental principles. The proposed model is simulated in the MATLAB/Simulink environment and experimentally verified.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: Bars; Integrated circuits; Maximum Power Point Tracking; Microcontroller; Microgrid; Power electronics; Topology; Voltage; Voltage control; Microgrids; Quadratic Boost Converter